Effectiveness of digital interventions with application program to improve nutritional knowledge, mother's behavior and nutrition status of children under five : A systematic review - Madinatul Munawwaroh; Sapja Anantanyu; Sumardiyono Sumardiyono (Indonesian Nutrition Association, 2022)
The problem of under-five nutrition is still a significant concern in developing countries, including Indonesia. Under-five nutritional problems are caused by multifactorial causes, therefore, nutrition education can be the key to intervention in children’s nutrition problems. With the current development of technology, it will be easier to intervene in nutritional problems through digital platforms, for example, using applications. This review aimed to analyze the effectiveness of digital interventions through applications on nutritional knowledge, mother’s behaviour, and nutritional status of children under-five